Revisiting the Incidence and Risk Factors for Cervical Postlaminectomy Kyphosis - Takashi Hirase; Colten Rowan; Thomas Jacob; Max Sadlowski; Sree M. Vemu; Austin Nguyen; Gregory S. Kazarian; Kevin J. DiSilvestro; Rex A.W. Marco; Todd J. Albert; Han J. Kim (Clinical Spine Surgery, 2026)
Study Design: Systematic review. Objective: To perform a systematic review that investigates the incidence and risk factors for cervical postlaminectomy kyphosis. Summary of Background Data: There is a wide range of incidences and risk factors for cervical postlaminectomy kyphosis reported within the literature. Definitive recommendations on indications and technical considerations to minimize this complication remain elusive. Methods: A systematic review was registered with PROSPERO and conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. All level I–III evidence studies investigating radiologic outcomes after cervical laminectomy for compressive pathology of the cervical spine were included. Results: Twenty studies with 1538 patients (1007 males, 531 females) were included. Extensive laminectomy (≥4 laminae) was performed in 746 patients (48.5%), selective laminectomy (